2010
DOI: 10.5301/ejo.2010.6112
|View full text |Cite
|
Sign up to set email alerts
|

Do Adherence Rates and Glaucomatous Visual Field Progression Correlate?

Abstract: Our data suggest that adherence rate may play a role in glaucomatous damage and/or progression; the target IOP therefore should be adjusted by adherence rates. Monitoring tools, educational programs, use of videos, a better doctor-patient relationship, or other means to improve adherence are desirable and necessary to preserve visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 30 publications
0
112
0
Order By: Relevance
“…Participants were more often female (63.7% versus 49.3%), χ 2 (2) = 4.44, p = .04, African-American (19.9% versus 6.0%), χ 2 (2) = 4.71, p = .03, and slightly younger ( M = 65.0 years versus 69.9), t (251) = 2.69, p = .008, than those who refused participation. There were no differences between participants and nonparticipants in the percentage of Latino/Latina patients or the percentage of patients with insurance ( ps > .65).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were more often female (63.7% versus 49.3%), χ 2 (2) = 4.44, p = .04, African-American (19.9% versus 6.0%), χ 2 (2) = 4.71, p = .03, and slightly younger ( M = 65.0 years versus 69.9), t (251) = 2.69, p = .008, than those who refused participation. There were no differences between participants and nonparticipants in the percentage of Latino/Latina patients or the percentage of patients with insurance ( ps > .65).…”
Section: Resultsmentioning
confidence: 99%
“…Eye drop medications are prescribed to preserve visual function and quality of life by reducing intraocular pressure (IOP), and regular eye drop use reduces the rate of glaucoma progression (2). However, nonadherence is an ongoing barrier to glaucoma treatment (3,4), with more than half of patients remaining nonadherent even after significant vision loss (5).…”
mentioning
confidence: 99%
“…In a randomized clinical trial testing whether interventions can improve rates of adherence (as determined by an electronic dosing aid device), investigators found no significant difference in IOP between the intervention and observation groups, although adherence increased by 20%. 96 On the other hand, Rossi et al 97 retrospectively investigated the relationship between visual field progression and adherence rate in patients with glaucoma using an electronic dosing aid device. Seventy-one percent of patients with stable visual fields had a median adherence rate of 85%, whereas patients who progressed (29%) recorded a median adherence of 21%.…”
Section: Difficulties In Evaluating the Rate Of Progressionmentioning
confidence: 99%
“…What is known is that not all glaucoma patients adhere with their therapy all of the time, and there is growing evidence that this situation correlates with worse control of IOP, greater fluctuations in IOP and worsening of visual field defects [110][111][112][113]. Clinical studies have also shown that glaucoma patients who discontinue their medical therapy tend to do so within the first 6 months after initiation of treatment, indicating poor persistence with therapy [114,115].…”
Section: Adherence and Persistencementioning
confidence: 99%